Isolated Optic Perineuritis as the Presenting Sign of Sarcoidosis. Issue 2 (June 2020) - Micieli, Jonathan A.; Streutker, Catherine J.; McIntyre, Kieran
Abstract : Abstract: A 35-year-old healthy African-American woman presented with a 4-month history of gradual loss of vision in the right eye from an optic neuropathy. MRI of the orbits with gadolinium showed isolated thickening and enhancement of the right optic nerve sheath. Chest x-ray and CT-scan of the chest were performed and showed bilateral hilar and mediastinal lymphadenopathy. This was suggestive of sarcoidosis, and the diagnosis was confirmed with histopathology. The patient promptly recovered vision with high-dose corticosteroids; the thickening of the optic nerve sheath also regressed. Isolated optic nerve sheath thickening from sarcoidosis is rare and may mimic compressive optic neuropathies such as optic nerve sheath meningiomas. A systemic evaluation for systemic inflammatory etiologies should be considered in such cases.